Determination of Cytotoxicity Properties of Oxime-Cyclotriphosphazene Derivatives Against PC-3 Cancer Cell Lines - Calisgan, Seyma; Beytur, Asiye; Menengic, Kubra Nur; Tekin, Suat; Koran, Kenan; Gorgulu, Ahmet Orhan; Sandal, Suleyman (Wiley, 2017)
[Abstract Not Available]
Keywords: Structural-Characterization